Relation of Body Mass Index (BMI) with Physical Activity of Students and Gender Differences - Špehar, Natalija (Array, 2012)
The goal of this study is to examine influence of physical activities over 7 or 30 days, with minimum duration of 30 minutes every day, on BMI of students and to establish gender difference. Random sample of 745 students (568 female and 177 male) in 1st year (freshmen) of undergraduate study at Faculty of Humanities and Social Sciences at University of Zagreb. Data is collected through voluntary and non-anonymous survey. The entire survey consists of 26 questions or which 5 are used in this study. No data transformation was applied prior to our analysis. We use basis statistical methods for description of student population. The difference between male and female students is assessed by t-test (p<0.05) and results show existence of statistically significant difference between genders in level of physical activities and BMI. Multiple regression analysis between BMI and the predictor variables describing student practice of sport show no statistically significant relation. This study confirms previous findings of insufficient level of physical activity among students and that BMI with normal values is not the most relevant indicator of health and fitness.